Framing the Sudanese Refugee Flows to Egypt Across Traditional and Social Media. - Abdullah, Ghada (AUC Knowledge Fountain, 2025)
This thesis examines the framing of Sudanese refugees in Egyptian media during the first year of the Sudanese conflict (April 2023–March 2024). Employing a content analysis framework, the research investigates content from three Egyptian newspapers—Al Ahram, Al Masry Al Youm, and Al Wafd—alongside tweets from the social media platform X. The study identifies recurring frames, themes, and narratives, highlighting differences between traditional media and social media platforms in their portrayal of Sudanese refugees. Key findings reveal that neutral tone dominate traditional media, focusing on factual reporting, followed by negative, then positive tones. Conversely, social media predominantly features negative narratives, such as social rejection, mass influx and economic strain, reflecting public fears and stereotypes. The most dominant frames found in online media were the mass influx, economic threat, and vulnerability frames. While unique frames on social media, including humanitarian advocacy and call for actions, demonstrate its potential for mobilization and raising awareness. Although social media allows the opinion of normal people to appear, yet concerns around its credibility remain a critical issue. Recommendations include fostering more balanced and inclusive media representation of refugees, emphasizing transparency, and addressing public concerns through informed coverage.